SDN architecture for UAVs and EVs using satellite: A hypothetical model and new challenges for future - Muhammad Reazul Haque; Saw Chin Tan; Zulfadzli Yusoff; Kashif Nisar; Ching Kwang Lee; BS Chowdhry; Sameer Ali; Shuaib K. Memona; Rizaludin Kaspin (IEEE, 2021)
Software-Defined Networking (SDN) the upcoming popular, reliable, and agile networking for the future. The programmability and centralized control system of SDN attracted many researchers, scientists, and industries to do research and implement it. At the same time, the programmability of Unmanned Aerial Vehicle (UAV) and self-driving Electric Vehicle (EV) are becoming the focal point of future transportation and security. In this paper, we proposed a hypothetical model of SDNUAV- EV architecture to implement SDN with Unmanned Aerial Vehicle (UAV) and self-driving Electric Vehicle (EV) using Satellite which is cost-effective for satellite link budget and SDN architecture.